FORMULASI DAN UJI KELAYAKAN SEDIAAN KRIM ANTI INFLAMASI GETAH TANAMAN PATAH TULANG (Euphorbia tirucalli L) - Agral, Omega; Fatimawali, Fatimawali; Yamlean, Paulina V.Y; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACT Has been formulated the latex of pencil tree plant (Euphorbia tirucalli L) to be a cream. Pencil tree plant latex cream formulated with various concentrations of the active substances i.e 5%, 10%, and 15%. The formulation of pencil tree plant latex cream produced the cram with good parameter values. Key words : Cream, Pencil Tree Plant (Euphorbia tirucalli L)